Exclusion of Anemone tetrasepala (Ranunculaceae) from the flora of China - Yuan, Qiong; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2018)
We demonstrate that all the Xizang (Tibet) specimens previously identified as Anemone tetrasepala (Ranunculaceae) actually belong to A. elongata, a species distributed in east Himalaya. Anemone tetrasepala is not known to occur in China, but is confined to north-west Himalaya only.